PENGARUH KUALITAS AUDIT TERHADAP AUDIT REPORT LAG (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2017-2018) - Dionisius Raditya Yogiputra; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2021)
This study was made with the aim of knowing the effect of audit quality, which consists of auditor industry specialization and auditor reputation, on audit report lag in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the period of observation from 2017 to 2018. Independent variables on this research are auditor industry specialization and auditor reputation, the dependent variable in this study is audit report lag, and the control variables in this study are company size, financial leverage, number of subsidiaries, extraordinary items, family ownership, financial condition, and the type of industry.This study has a population that is all companies listed on the Indonesia Stock Exchange (IDX). The sample in this study consisted of all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017–2018, with a total sample of 565 companies samples. Purposive sampling menthod is a method used to take samples that will be used in this study. Sources of data used in this study are secondary data from audited financial reports and company annual reports published through the Indonesia Stock Exchange (IDX) website as well as through the respective companies' websites. Ordinary Least Squares (OLS) and multiple regression techniques are the analytical methods used in this study.The results obtained in this study indicate that there is a negative but insignificant influence between the auditor industry specialization and audit report lag, and there is a negative but insignificant effect between the auditor reputation and audit report lag.